Pengaruh Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Burgerking Cabang Plazapondok Indah - Bintang Danu Saputra; Ade Ratna Sari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - The purpose of this study was to determine the effect of Price and service quality on Purchasing Decisions at BurgerKing Plaza Pondok Indah Branch. The research method used is a quantitative method. The sampling technique used in this study was 100 respondents. Data analysis techniques with instrument tests, namely validity tests and reliability tests, classical assumption tests, namely normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, simple linear regression tests, multiple linear regression tests, correlation coefficient tests, determination coefficient tests and hypothesis tests, namely t-tests and f-tests. The results of this study are that price has a significant effect on purchasing decisions with the hypothesis test obtained a T count value> T table (5.947> 1.664). Service quality has a significant effect on purchasing decisions with the hypothesis test obtained a T count value> T table (8.143> 1.664). Price and service quality simultaneously have a significant effect on purchasing decisions with the hypothesis test obtained a F count value> F table or (33.932> 3.94). Thus it can be concluded that price and service quality have a positive and significant effect on purchasing decisions at BurgerKing. The coefficient of determination has an effect or contributes to a simultaneous effect of 0.412 or 41.2% while the remaining 58% is influenced by other factors.